Dinamika Keilmuan di Pesantren Lirboyo Kediri - Ali Anwar (Al-Riwayah : Jurnal Kependidikan, 2015)
Islamic Boarding School (Pesantren) of Lirboyo, founded in 1910, transmits the Islamic and general knowledge. The methods to transmit the knowledge are bandongan, sorogan, memorizing, discussion, ba’sul masā’il, and other methods which are commonly used in formal education. By this finding, we can conclude that Pesantren Lirboyo up to now can admit the basic functions of pesantren instituion. Those are transmission of Islamic kndwledge, maintenance of Islamic tradition, and reproduction of ulama’.